Imaging of Acute Invasive Fungal Rhinosinusitis in a Patient with Gorlin Syndrome and Acute Lymphocytic Leukemia. (18th June 2013) - Donovan, S. T.; Thompson, J. W.; Sandlund, J. T.; Adderson, E. E.; Pivnick, E. K.; Harreld, J. H.
Abstract : Gorlin Syndrome (GS), also known as nevoid basal cell carcinoma syndrome, is a rare autosomal dominant condition characterized by developmental abnormalities and predisposition to certain neoplasms. Acute invasive fungal rhinosinusitis (AIFRS) is an uncommon clinical entity characterized by high morbidity and mortality. In immunocompromised patients, computed tomography plays a critical role in screening for suspected AIFRS. However, due to the association between exposure to ionizing radiation and subsequent development of malignancies in patients with GS, patients with GS and suspected AIFRS present a unique and challenging clinical scenario. We present a case of a pediatric patient with GS and acute lymphocytic leukemia (ALL) diagnosed with AIFRS; to the best of our knowledge, it is the only case described in the literature.